Comparison of Examination Result of Streptococcus Results Β Hemolyticus in Throat Swab Culture Method and Rapid Antigen Detection Test (RADT) in Tonsillitis Patient - Pramonodjati, F.; Yatim, Nurulshyha Md; Rahmawati, Selvina Dwi (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Tonsillitis can be caused by bacteria and virus. The bacteria that most commonly causes tonsillitis is Streptococcus β hemolytic. Diagnose of tonsillitis is very important to ensure the cause in order to conduct appropriate treatments, so avoid unnecessary use of antibiotics. Diagnostic test that can be applied to determine the causes of tonsillitis are throat swab culture method and RADT. The purpose of this study was to investigate the presence of Streptococcus β hemolyticus as the cause of tonsillitis using throat swab culture method and RADT This study was observational analytic with cross sectional approach. Patients who met inclusion criteria and exclusion criteria then tested using throat swab culture and RADT. Data obtained in this research was processed with statistical analysis techniques. Data did not distributed normally using nonparametric test, i.e. Mann-Whitney test. In this research obtained 30 samples tonsillitis patient, which tested by culture and RADT methods. Results between culture and RADT compared. Result from culture method obtained 11 samples of patient was positive Streptococcus β hemolyticus and 16 samples of patient was positive Streptococcus β hemolyticus of RADT method. Statistical analysis showed that there was significant differences between the examination result of throat swab method and RADT.